Slavery, Sex Work, and a Materialist Reconceptualization of Islamic Marriage - Musleh, Samira (Journal of the American Academy of Religion, 2025)
Islamic marital payments are sometimes praised for privileging women, at times criticized for advantaging men, occasionally tokenized. Using three sets of case studies from Bangladeshi media, this article examines how discrepancies in these discourses on such payments mirror scholarly attempts to categorize them as gifts, prices, or wages. Drawing on feminist debates on the ethics of transacting sex for money in the market through sex work and transhistorical criticisms of marriage as a state of unfreedom, I theorize the tension between labor compensation and power dynamics in relationships born at the crux of gender and economic disparities. Departing from propositions to correct a presumed power imbalance created by unilateral payments by either rearticulating the marital relationship as one of business partnership or eliminating these payments altogether, I argue that it is instead through a materialist interpretation of marital payments as compensations for reproductive labor that a reconceptualization of Islamic marriage is possible.